Práticas de leitura de alunos do Curso de Letras da UFC reveladas em suas narrativas de vida em seu memorial de formação - Lima, Priscila Sandra Ramos de (2019)
The aim of this Dissertation was to analyze how the reading practices of teachers in initial formation, students of the Course of Languages of the Federal University of Ceará (UFC), developed from the construction of memorials produced in the discipline of Biographies in 2018.1, in view of their life narratives and reading formation. Therefore we have established the following specific objectives: to identify the practices, places and modes of reading developed by the students collaborating in the study along their life trajectories and formation; understand how the socioeconomic, cultural, family and school / academic contexts in which the participants were and are inserted focus on their reading practices and analyze the set of characteristics and meanings of the autobiographical narrative saying constructed by the writers of the reading memorials in study. The theoretical foundations on which these objectives were based on Bakhtin's (2003, 2009, 2010) postulates of the conceptions of the researchers who study life history and formation, who are Josso (2010), Maia-Vasconcelos (2016), Passeggi (2008; 2010), Vasconcelos (2011), as well as the contributions of studies that focus on reading, such as Chartier (1999), Freire (2005), Jouve (2002), Lajolo and Zilberman (1999), Manguel (1997), Martins (1997) and Petit (2013). Methodologically, we use the perspective of Life History and Formation elaborated by Josso (2010). In light of this approach, we proceeded with the qualitative analysis of the corpus consisting of five reading training memorials written by students of the Course of Languages, in the discipline of Biographies offered in 2018.1. From an intuitive horizontal analysis of the data, the following categories were constructed: reading practices in childhood, reading practices in adolescence, reading practices in the undergraduate course, being a student of the public school, access to books and the mother as incentive for reading. Then, we performed a vertical analysis of the memorials that allowed us to arrive at the following results: the reading presents significant dimensions of affective values, repairers and transformers that are peculiar in the life trajectory of each subject. We conclude that reading can permeate and strengthen affective relationships, provide a healing effect in times of physical and psychological pain and suffering, as well as being able to transform a whole life story.